(3GdHgLI GdeQVjI aj TQM GdCdajIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3SdjeGf Hf Ydi Hf MSf GdHMjQi s)
(3ChdgG (B:s
(3gPG TQM dWja eRLJg HCdajg GHf eGdc , ePgH GdebGUO hGVM GdeSGcd , jHjf eQGO fGXegG , hjgOi GdWGdH HgG Edi eYGdegG SejJg HGdfgLI GdeQVjI , ai TQM GdCdajI s
(3BNQgG (B:s
(3hbO bGd GHf YHGS QVi Gddg YfgeG eG ChJi YGde YdekG hgh TGH hGdMeO ddg GdPi gOGfG J e TQM GdCdajI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG JUMjMGJs
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs